Defoliation patterns and tillering dynamics in Italian ryegrass under different herbage allowances - Larissa Arnhold Graminho; Marta Gomes da Rocha; Luciana Pötter; Aline Tatiane Nunes da Rosa; Tuani Lopes Bergoli; Marcela Machado (Acta Scientiarum. Animal Sciences, 2014)
This work was carried out in order to generate information on the tillering process and to contribute for the understanding of the defoliation process on Italian ryegrass (Lolium multiflorum Lam.) grazed by lambs under different herbage allowances: 6, 8 and12 kg  of dry matter  per100 kg of animal live weight  per day. The grazing method was intermittent. The experimental design was completely randomized following a repeated measure arrangement, with three treatments and two area replications. The intensity of defoliation is greater at 6 and 9% herbage allowances. The defoliation interval is higher at 12% herbage allowance, intermediate at 9% and lower at 6%. The rates of tiller emergence, survival and death, stability index the tiller population are similar for the different herbage allowances and differ according to the phenological stage of ryegrass. Structural changes caused by canopy management with low herbage allowance and/or due to the advance in developmental stage of ryegrass alter defoliation strategies, with more intense and frequent grazing.